Ekofilozoficzne wątki w antropologii M. Schelera, H. Plessnera, A. Gehlena - Płachciak, Adam (The Ecophilosophical Threads in the Anthropology by M. Scheler, H. Plessner and A. Gehlen, 2005)
The article is an attempt of investigating the connections between ecophilosophy and philosophical propositions of the anthropology by M. Scheler, H. Plessner and A. Gehlen. They try to overcome classical propositions of metaphysics by Descartes, being metaphysic of the subject and the metaphysic of subjectivity by Aristotle. They promote relative attitude between man and nature.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 109-117